The Relationship between Myoglobin, Aerobic Capacity, Nitric Oxide Synthase Activity and Mitochondrial Function in Fish Hearts - Lucie Gerber; Kathy A. Clow; William R. Driedzic; Anthony K. Gamperl (MDPI AG, 2021)
The dynamic interactions between nitric oxide (NO) and myoglobin (Mb) in the cardiovascular system have received considerable attention. The loss of Mb, the principal O2 carrier and a NO scavenger/producer, in the heart of some red-blooded fishes provides a unique opportunity for assessing this globin's role in NO homeostasis and mitochondrial function. We measured Mb content, activities of enzymes of NO and aerobic metabolism [NO Synthase (NOS) and citrate synthase, respectively] and mitochondrial parameters [Complex-I and -I+II respiration, coupling efficiency, reactive oxygen species production/release rates and mitochondrial sensitivity to inhibition by NO (i.e., NO IC50)] in the heart of three species of red-blooded fish. The expression of Mb correlated positively with NOS activity and NO IC50, with low NOS activity and a reduced NO IC50 in the Mb-lacking lumpfish (Cyclopterus lumpus) as compared to the Mb-expressing Atlantic salmon (Salmo salar) and short-horned sculpin (Myoxocephalus scorpius). Collectively, our data show that NO levels are fine-tuned so that NO homeostasis and mitochondrial function are preserved; indicate that compensatory mechanisms are in place to tightly regulate [NO] and mitochondrial function in a species without Mb; and strongly suggest that the NO IC50 for oxidative phosphorylation is closely related to a fish's hypoxia tolerance.